Molecular characterization of Cratylia argentea accessions and its phylogenetic relationship with other legumes - Galdino, Alexsandro Sobreira; Lima, João Paulo Matos Santos; Antunes, Renata de Souza Panarari; Prioli, José Alberto; Thiers, Paulo Roberto; da Silva, Glocimar Pereira; Grangeiro, Thalles Barbosa (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to molecularly characterize 11 Cratylia argentea accessions, ITS (ITS1/5.8S/ITS2) region as well to establish its phylogenetic relationship using a gene sequence that codes the subunit 18S of the rRNA (rDNA 18S). DNA amplification of the ITS/5.8S region of these 11 accessions revealed an amplicon with around 650 bp. ITS/5.8S sequences were obtained from all accessions analysed, and then aligned with the region ITS/5.8S of Galactia striata legume. The size of ITS/5.8S region ranged from 565 to 615 bp. Average G + C contents in the ITS1 and ITS2 regions ranged between 46 and 47%. The multiple sequence alignment between the ITS sequences from C. argentea accessions and Galactia striata revealed the presence of deletions and insertions. C. argentea accessions formed a unique politomic clade. Cratylia argentea phylogenetic analysis demonstrated that this species is placed into the true Diocleinae Clade, and that Calopogonium and Pachyrhizus are not included in subtribe Diocleinae.